Evaluating IT Capabilities in The Success of Pipe Manufacturing Company - Holman, Jason Nathanael; Desanti, Ririn Ikana (ULTIMA InfoSys, 2024)
Information technology (IT) management is a process that a corporation or organization must carry out, particularly in terms of data management. The research employs a case study of a pipe manufacturer that has implemented a human resources system to manage employee information. To avoid problems in the data management process that can impede company performance, the company must have good information technology governance capabilities in the data management process. This research will focus on measuring and evaluating the capability of information technology governance at the company, as well as making recommendations to improve the company's existing IT governance. The COBIT 2019 framework will be used to assess the company's IT governance capabilities using qualitative data collected from collaborative interviews with the company and supported by previous research literature. The measurement focus will be on IT infrastructure for data management and operations management to support the data management process. APO01 - Managed I&T Management Framework, APO14 - Managed Data, and DSS01 - Managed Operations are the COBIT 2019 processes to be monitored. The study's findings include the realization of IT governance capabilities in the APO01 domain and a lack of IT governance capabilities in the other two domains, namely APO14 and DSS01. The capability level is stopped at level 2 for the APO14 and DSS01 domains, which is one level below the declared aim of level 3. The recommendations will center on enhancing the IT governance skills of the two domains that fail to meet the company's capability targets.